Unconventional Pedagogical and Educational Approaches at Chosen Alternative Schools During the Period of Czechoslovak Republic (1918-1939) - Lukáč, Eduard (Wydawnictwo Naukowe UAM, 2016)
The reform pedagogical movement in the period of the Czechoslovak Republic (CSR) helped educators to change standard pedagogical and educational approaches, which were typical of the Herbarttype schools. The paper concentrates on the analysis of pedagogical activities of chosen members of this movement in the first decade of the new state. They were inspired by the ideas of important world personalities such as J. Dewey, M. Montessori, E. Key, H. Parkhurst, etc., and were active in individual alternative classes, resp. schools, but their activity was limited to them only as they did not find any continuators of their effort in the period under consideration.
Niekonwencjonalne podejście pedagogiczne i edukacyjne w wybranych szkołach alternatywnych w okresie istnienia Czechosłowacji (1918-1939)
Keywords: reform pedagogical movement; alternative classes; alternative schools